2014
DOI: 10.3171/2014.6.spine13448
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic renal cell carcinoma, with a radiographically occult primary tumor, presenting in the operative site of a thoracic meningioma: long-term follow-up

Abstract: Lesions metastatic to the site of a meningioma resection from a different primary tumor are rare. Metastasis of a tumor without a known primary tumor is also rare. Metastasis of a renal cell carcinoma, without an identifiable primary tumor, to the bed of a meningioma resection has not been previously reported. The authors describe the case of a 54-year-old man who presented with decreased sensory and motor function in the lower extremities. He underwent T3–5 laminectomies and gross-tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
(32 reference statements)
0
9
0
1
Order By: Relevance
“…While the development of metastatic disease without an identifiable primary malignancy is extremely rare, there have been three well-documented cases of RCC presenting as metastatic disease without a renal primary, to our knowledge [5, 8, 9]. Johnson et al [9] reported a case of metastatic RCC to the adrenal gland, with an associated involuted region of the ipsilateral kidney which was proposed to represent spontaneous regression of the primary tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the development of metastatic disease without an identifiable primary malignancy is extremely rare, there have been three well-documented cases of RCC presenting as metastatic disease without a renal primary, to our knowledge [5, 8, 9]. Johnson et al [9] reported a case of metastatic RCC to the adrenal gland, with an associated involuted region of the ipsilateral kidney which was proposed to represent spontaneous regression of the primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis in both of these cases was supported by well-differentiated clear cell morphology and immunohistochemical staining. Heary et al [8] reported a case of metastatic RCC arising in an epidural meningioma resection site 3 years after initial surgery, with no radiographic evidence of an occult renal primary. Herein, we report a case of poorly differentiated renal cell carcinoma that presented as bilateral adrenal and liver metastases without evidence of a renal primary.…”
Section: Discussionmentioning
confidence: 99%
“…However, presenting with mRCC with an undetectable primary is infrequent. A total of 12 cases were documented based on our literature review [5][6][7][8][9][10][11][12]; none of which had diffuse lymphadenopathy metastasizing from an unidentifiable renal primary as presented in our case. In such a challenging situation, immunohistochemical profiling as well as the promising field of molecular genetics aid in reaching a diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Upon reviewing the literature, a total of 12 cases of metastatic kidney cancer had no evidence of a renal mass [5][6][7][8][9][10][11][12]. In this case report, a case of mRCC with an initial presentation of generalized lymphadenopathy with an undetectable primary will be presented.…”
Section: Introductionmentioning
confidence: 99%
“…This entity has only rarely been described in the literature. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Renal-cell carcinoma (RCC) is a group of cancers arising from the nephron, where 70% of RCC are clear-cell RCC. Because of mutation in the Von Hippel-Lindau gene, a high amount of vascular endothelial growth factor (VEGF) is produced, resulting in increased angiogenesis, cell growth, metabolism, and immunesuppression.…”
Section: Introductionmentioning
confidence: 99%